Islamic Economy Implementation and Digital Creative Economy Development: The Mediating Role of Digital Innovation Capability in Culinary SMEs - Anisa Nikmatika; Moh. Mukhsin (Dinamis : Journal of Islamic Management and Bussiness, 2026)
The rapid growth of the digital creative economy has transformed the competitive landscape for culinary small and medium-sized enterprises (SMEs), creating opportunities for innovation while increasing the need for sustainable and ethical business practices. Although digital transformation has enhanced business performance, the integration of Islamic economy principles with digital innovation remains underexplored. This study aims to systematically review the existing literature on the relationship between Islamic economy implementation, digital innovation capability, and digital creative economy development. A qualitative Systematic Literature Review (SLR) was conducted using the PRISMA 2020 reporting guideline and the SPAR-4-SLR protocol to identify, evaluate, and synthesize relevant peer-reviewed studies published in reputable academic databases. The findings reveal that Islamic economy implementation functions as a strategic intangible resource that promotes ethical governance, stakeholder trust, and sustainable value creation. Furthermore, digital innovation capability acts as a key mediating mechanism by enabling culinary SMEs to transform Islamic business values into innovative products, services, and digital business models that support digital creative economy development. The review also highlights that integrating the Resource-Based View and Dynamic Capability Theory provides a comprehensive explanation of how ethical organizational resources are converted into sustainable competitive advantage through innovation. This study contributes by proposing an integrated conceptual framework that enriches the literature on Islamic economics, digital innovation, and digital entrepreneurship while offering practical insights for policymakers and culinary SMEs in strengthening sustainable digital transformation.   Keywords: Islamic economy implementation; digital innovation capability; digital creative economy; culinary SMEs; systematic literature review